Договоры и соглашения на английском: обучение чтению и анализу сложных текстов. - Medetova Gaukhar (Periodica Journal, 2024)
The article explores methods for teaching the reading and analysis of international treaties in English, which are key documents in the fields of international law and diplomacy. The significance of understanding treaty structure (preamble, operative clauses, final clauses) and linguistic features, such as formal style, the use of modal verbs (shall), complex grammatical constructions, and rich legal terminology, is emphasized. The author proposes practical tasks aimed at developing skills in analyzing, translating, and interpreting legal texts. Real international treaties are used as examples, providing practical value to the training. The proposed methodologies will help students, lawyers, and translators effectively work with international legal documents, avoiding errors in their interpretation
Keywords: международные договоры; юридический английский; анализ текста